How Employer Branding Shapes Person-Organization Fit in Gen Z: The Strategic Role of Social Media: JEL Classification: D22, G21, M31, O16, L26 - Salma, Arinda; Erlin, Nia Ariyani (Newinera Publisher, 2025)
As the world continues to develop and change, generations and intergenerational expectations are also changing. One of them is Generation Z, which shows unique characteristics in choosing a job, prioritizing the alignment of values and company culture. This study aims to examine the effect of employer branding on person- organization fit (P-O fit) in Generation Z job seekers, with social media as a mediating variable. The method used in this study is a quantitative approach with data collection through a questionnaire distributed online to 136 respondents who met the research criteria. The results of the analysis using SmartPLS show that employer branding has a positive and significant effect on P-O fit, and social media plays an important role in increasing this influence. These findings emphasize that companies need to build a strong and transparent image through social media to attract and retain Generation Z talent. This study provides insight for companies in formulating effective recruitment strategies in a competitive labor market.